Cognitive compensatory processes of older, clinically fit patients with hematologic malignancies undergoing chemotherapy: A longitudinal cohort study. Issue 12 (16th May 2017) - Libert, Yves; Borghgraef, Cindy; Beguin, Yves; Delvaux, Nicole; Devos, Martine; Doyen, Chantal; Dubruille, Stéphanie; Etienne, Anne‐Marie; Liénard, Aurore; Merckaert, Isabelle; Reynaert, Christine; Slachmuylder, Jean‐Louis; et al.
Abstract: Objective: Despite the well‐known negative impacts of cancer and anticancer therapies on cognitive performance, little is known about the cognitive compensatory processes of older patients with cancer. This study was designed to investigate the cognitive compensatory processes of older, clinically fit patients with hematologic malignancies undergoing chemotherapy. Methods: We assessed 89 consecutive patients (age ≥ 65 y) without severe cognitive impairment and 89 age‐, sex‐, and education level‐matched healthy controls. Cognitive compensatory processes were investigated by (1) comparing cognitive performance of patients and healthy controls in novel (first exposure to cognitive tasks) and non‐novel (second exposure to the same cognitive tasks) contexts, and (2) assessing psychological factors that may facilitate or inhibit cognitive performance, such as motivation, psychological distress, and perceived cognitive performance. We assessed cognitive performance with the Trail‐Making, Digit Span and FCSR‐IR tests, psychological distress with the Hospital Anxiety and Depression Scale, and perceived cognitive performance with the FACT‐Cog questionnaire. Results: In novel and non‐novel contexts, average cognitive performances of healthy controls were higher than those of patients and were associated with motivation. Cognitive performance of patients was not associated with investigated psychological factors in the novel context but was associated with motivation and psychological distress in the non‐novel context. Conclusions: Older, clinically fit patients with hematologic malignancies undergoing chemotherapy demonstrated lower cognitive compensatory processes compared to healthy controls. Reducing distress and increasing motivation may improve cognitive compensatory processes of patients in non‐novel contexts.